2013
DOI: 10.1057/jors.2012.123
|View full text |Cite
|
Sign up to set email alerts
|

A combined statistical approach and ground movement model for improving taxi time estimations at airports

Abstract: With the expected continued increases in air transportation, the mitigation of the consequent delays and environmental effects is becoming more and more important, requiring increasingly sophisticated approaches for airside airport operations. Improved on-stand time predictions (for improved resource allocation at the stands) and take-off time predictions (for improved airport-airspace coordination) both require more accurate taxi time predictions, as do the increasingly sophisticated ground movement models wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
55
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(61 citation statements)
references
References 14 publications
1
55
0
Order By: Relevance
“…In previous ground movement research, average taxi speeds have been assumed to be influenced only by the aircraft type, however, taxi time research has shown that the aircraft type is not the most influencing factor upon taxi speeds (Ravizza et al 2012;Idris et al 2002;Rappaport et al 2009). Comparisons between ground movement tool results and the status quo at airports have previously been hard to analyse, due to the need for accurate taxi speed data.…”
Section: Taxi Time Predictionmentioning
confidence: 99%
See 3 more Smart Citations
“…In previous ground movement research, average taxi speeds have been assumed to be influenced only by the aircraft type, however, taxi time research has shown that the aircraft type is not the most influencing factor upon taxi speeds (Ravizza et al 2012;Idris et al 2002;Rappaport et al 2009). Comparisons between ground movement tool results and the status quo at airports have previously been hard to analyse, due to the need for accurate taxi speed data.…”
Section: Taxi Time Predictionmentioning
confidence: 99%
“…An approach to more accurately predict taxi times for aircraft or, equivalently, their average speeds, was proposed in Ravizza et al (2012). Multiple linear regression was used to estimate a more accurate taxi speed prediction function and identify the factors which were most related to taxi speeds, such as total distance travelled, total turning angle and the number of other aircraft of different types which were moving around the airport at the time.…”
Section: Taxi Time Predictionmentioning
confidence: 99%
See 2 more Smart Citations
“…to control the demand. S Ravizza et al (2013) and Lordan, Sallan, and Valenzuela-Arroyo (2016) in their study highlight the necessity of more accurate airport taxi time estimation to reduce delays and environmental impacts of airport operations. According to CODA (Central Office for Delay Analysis) (Eurocontrol 2016a), delay causes are categorized to airline (e.g.…”
Section: Airport Operations and Managementmentioning
confidence: 99%